Chemical and Organoleptic Analysis of Tiliaya Products Fortified Yellow Pumpkin (Cucurbita moschata Durch) - Bait, Yoyanda; Nalole, Jihan Alqirah; Liputo, Siti Aisa; Saman, Widya Rahmawaty (Program Studi Teknologi Hasil Pertanian, Politeknik Gorontalo, 2023)
Tiliaya is a type of traditional food in Gorontalo. Its existence has been around for a long time and has become a hereditary legacy in Gorontalo and is only found in traditional ceremonies or certain religious rituals. In addition, most of the tiliaya circulating in the market are tiliaya without certain nutritional fortifications. The purpose of this lab is to find out the characteristics of tiliaya fortified with pumpkin. The design used was a completely randomized design (CRD) with 1 control and 3 treatments. Each control and treatment will be repeated 3 times. T0 without adding pumpkin, T1 adding 10% pumpkin, T2 adding 20% ​​pumpkin and T3 adding 30% pumpkin. The test parameters carried out included Vitamin C Test, Fiber Content and Organoleptic Preference Test. Based on the results, it was found that the increase in vitamin C content was from 2.93 to 5.86 mg/100, While the organoleptic characteristics of tiliaya include taste, color, texture and aroma. Tiliaya with the addition of 10% extract had the highest texture, color and aroma taste values.